Fiqh Syiah Syiah: Sejarah Awal, Perkembangan, dan Adaptasi dalam Modern Era - Maulidya Winatasya; Meinajwa Akbar; Sinar Kumala; Alencia Muryanti; Surya Sukti (Indo Publishing, 2026)
This article examines the development of Shi‘i political jurisprudence (fiqh siyasah) from its early emergence to its transformation in the modern era. The study highlights the historical roots of Shi‘i political thought, particularly its foundation in the doctrine of the Imamate, which distinguishes it from Sunni political theory. Using a qualitative literature-based approach, this research explores the evolution of Shi‘i political thought across the classical, medieval, and modern periods.The findings indicate that Shi‘i political jurisprudence has undergone significant transformation, particularly through the formulation of the doctrine of wilayat al-faqih, which integrates religious authority with modern state governance. Furthermore, this article compares Shi‘i and Sunni political jurisprudence, emphasizing differences in leadership legitimacy, authority structures, and adaptability to modern political systems.This study concludes that Shi‘i political jurisprudence demonstrates a dynamic capacity to adapt to contemporary political realities while maintaining its theological foundations.